Toxoplasma gondii: The severity of toxoplasmic encephalitis in C57BL/6 mice is associated with increased ALCAM and VCAM-1 expression in the central nervous system and higher blood–brain barrier permeability - Silva, Neide Maria; Manzan, Renato Martins; Carneiro, Wesley Pereira; Milanezi, Cristiane Maria; Silva, João Santana; Ferro, Eloísa Amália Vieira; Mineo, José Roberto (Experimental parasitology, 2010)
In order to investigate the differential ALCAM, ICAM-1 and VCAM-1 adhesion molecules mRNA expression and the blood–brain barrier (BBB) permeability in C57BL/6 and BALB/c mice in Toxoplasma gondii infection, animals were infected with ME-49 strain. It was observed higher ALCAM on day 9 and VCAM-1 expression on days 9 and 14 of infection in the central nervous system (CNS) of C57BL/6 compared to BALB/c mice. The expression of ICAM-1 was high and similar in the CNS of both lineages of infected mice. In addition, C57BL/6 presented higher BBB permeability and higher IFN-γ and iNOS expression in the CNS compared to BALB/c mice. The CNS of C57BL/6 mice presented elevated tissue pathology and parasitism. In conclusion, our data suggest that the higher adhesion molecules expression and higher BBB permeability contributed to the major inflammatory cell infiltration into the CNS of C57BL/6 mice that was not efficient to control the parasite.